The Qualitative Fundamental Motor Performance Characteristics of Preadolescent Obese Children - Smith, Steven; Morrison, Kyle; Bransdorfer, Elizabeth; Barthel, Samuel (International Journal of Child Health and Nutrition, 2016)
This study examined the qualitative motor performance characteristics of 35 preadolescent obese children (18 female, 17 male) in the Midwest of the United States. An available sample of children ages six to 13 were classified as obese based on a BMI score of 30 or greater. The Test of Gross Motor Development-2 (TGMD-2)was used to assess all subjects. This test measures the qualitative motor ability of children using two subtest categories of fundamental motor skills including locomotors (running, hopping, skipping, jumping, leaping and galloping) as well as object control skills (throwing, catching, kicking, bouncing a ball, rolling a ball and striking). All participants received a raw score, standardized score, sum of standards and gross motor quotient score. All scores were compared to national norms established by the authors of the TGMD-2. The results indicated that the group norms of the obese children were significantly below the mean scores of the national average for all measures including locomotor standard scores (M=3.80, SD=2.44, p<0.001) and object-control standard scores(M=4.43, SD=2.89, p<0.001)and the gross motor development quotient (M=64.69, SD=15.05, p<0.001).The researchers concluded that the significantly lower motor performance scores of obese children may lead this population to participate less in health enhancing movement opportunities as they grow into adolescence and adulthood. The authors noted that the TGMD-2 is designed for children ages 3-10 and has a significant ceiling effect for older children. A younger population may reveal more robust conclusions in further study. Additionally, further study is recommended to determine whether programs aimed at lowering obesity levels in children can have an impact on qualitative fundamental motor skill performance